Communication, Motivation, and Employee Performance: A Systematic Literature Review - Sherren, Vincentia; Indra, Ricardo (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Human resources are considered one of the most crucial assets for ensuring long-term sustainability and competitiveness of any organization or company. Employees who deliver high-quality performance make a significant impact on the company’s growth and success. Recognizing this importance, this study presents a conceptual model to understand the key factors influencing employee performance within organizational settings. The model examines the effects of communication, work environment, incentives, leadership style, and motivation on employee performance. This conceptual framework was developed based on a systematic literature review conducted in accordance with the PRISMA 2020 guidelines to ensure transparency and methodological rigor. Relevant studies published between 2016 and 2024 were evaluated based on predefined inclusion and exclusion criteria. The findings suggest that effective communication, supportive work environments, properly designed incentive systems, and appropriate leadership styles work together to enhance employee motivation, ultimately improving performance outcomes. These results imply that organizations should prioritize communication training, develop conducive workplace conditions, implement fair and achievable incentive structures, and adopt leadership approaches that strengthen both extrinsic and intrinsic motivation. Collectively, these implications highlight the importance of integrating organizational, psychological, and managerial strategies to optimize employee performance and long-term organizational success.